Building energy retrofit-as-a-service: a Total Value of Ownership assessment methodology to support whole life-cycle building circularity and decarbonisation. Issue 9 (2nd September 2022) - Azcarate-Aguerre, Juan Francisco; Conci, Mira; Zils, Markus; Hopkinson, Peter; Klein, Tillmann
Abstract: The regulatory drive to accelerate the clean energy and circular economy transitions in the European building stock is currently failing to overcome systemic implementation barriers. These barriers include high initial investment costs, misaligned financial incentives among stakeholders, and the relatively low cost of less sustainable energy and materials. A Product-Service Systems (PSS) approach could successfully overcome many of these barriers by (1) outsourcing capital investment, as well as financial and technical risks, (2) providing shared economic incentives to collaborating stakeholders, and (3) retaining extended producer responsibility and ownership over materials and products. However, PSS is still not seen as a viable business model when compared to both a standard "ownership" contract and a "no-retrofit" scenario. This paper proposes a Total Value of Ownership (TVO) method to evaluate the financial performance of a building energy retrofit in terms of Net Present Value, comparing a matrix of scenarios. Results show that – when accounting for capital and opportunity costs tied to alternative investments, internalising externalities, and monetising soft values such as user productivity and property value – a PSS model can deliver the highest NPV. Furthermore, results show that a PSS alternative can act as a positive future-proofing strategy to safeguard the building owner's position in the face of uncertain future market indicators and carbon taxation. Recommendations for policymakers, investors, financiers, building owners, and end-users are presented to identify the economic value of PSS contracts, leading to better-informed decisions which can accelerate deep energy retrofit of the building stock.